Roles of the respective loops at complementarity determining region on the antigen-antibody recognition. (October 2016) - Osajima, Tomonori; Hoshino, Tyuji
Graphical abstract: Highlights: ⿢ The direct hydrogen bond with the shortest distance is principally observed in the heavy chain. ⿢ Tyr in the heavy chain (especially at H2 and H3) primarily contributes to the binding free energy. ⿢ The appearances of Asn and Gln are large in the light chain. ⿢ Fab is more favorable than scFv for antigen-antibody interaction from the energetic viewpoint. ⿢ The length of H3 CDR loop has no correlation to the binding affinity. Abstract: For the rational design of antibody, it is important to clarify the characteristics of the interaction between antigen and antibody. In this study, we evaluated a contribution of the respective complementarity determining region (CDR) loops on the antibody recognition of antigen by performing molecular dynamics simulations for 20 kinds of antigen-antibody complexes. Ser and Tyr showed high appearance rates at CDR loops and the sum of averaged appearance rates of Ser and Tyr was about 20⿿30% at all the loops. For example, Ser and Tyr occupied 23.9% at the light chain first loop (L1) and 23.6% at the heavy chain third loop (H3). The direct hydrogen bonds between antigen and antibody were not equally distributed over heavy and light chains. That is, about 70% of the hydrogen bonds were observed at CDRs of the heavy chain and also the direct hydrogen bond with the shortest distance mainly existed at the loops of the heavy chain for all the complexes. It was revealed from the comparison in contribution to the binding free energy among CDR loops that the heavy chain (especially at H2 and H3) had significant influence on the binding between antigen and antibody because three CDR loops of the heavy chain showed the lowest binding free energy (ο G bind ) in 19 complexes out of 20. Tyr in heavy chain (especially in H2 and H3) largely contributed to ο G bind whereas Ser hardly contributed to ο G bind even if the number of the direct hydrogen bond with Ser was the fourth largest and also the appearance rate at CDR was the highest among 20 kinds of amino acid residues. The contributions ofTrp and Phe, which bear aromatic ring in the side chain, were often observed in the heavy chain although the energetic contribution of these residues was not so high as Tyr. The present computational analysis suggests that Tyr plays an outstanding role for the antigen-antibody interaction and the CDR loops of the heavy chain is critically important for antibody recognition of antigen.